How should we approach thyroidal incidentalomas detected on FDG-PET/ CT imaging? - Şimşek, Fikri Selçuk; Kuşlu, Duygu; Balcı, Tansel Ansal; Uğur, Kader; Koç, Zehra Pınar; Artaş, Hakan; Narin, Yavuz (My University, 2019)
Aim: Thyroidal incidentalomas (Tis) detected by F-18 fluorodeoxyglucose positron emission tomography/computed tomography(F-18FDG PET/CT) may be associated with three different causes that include metastasis of another malignancy, primary thyroidgland malignancies and lastly benign thyroidal nodules, all require different clinical approaches. For appropriate treatment, quickcharacterization of the Ti is important, preferably with a lesser invasive method. Our aim was to determine whether the characterizationof TIs can be performed with FDG-PET/CT, due to contribute faster diagnosis, and initiation of the therapy.Material and Methods: Forty-four patients with detected TIs in FDG-PET/CT were included in the study. The relationship betweenmetabolically/morphological parameters and pathology results were evaluated statistically. If two subsequent cytology werenegative, nodule accepted as benign. If cytology result was suspected or malignant, histopathological confirmation was made. Forthese patients, histopathological results were accepted as definite diagnosis.Results: Malignant thyroidal pathologies were detected in 29.5% of patients. We could not find any significant relationship betweenage, nodule size and SUVmax value and pathology results. According to ROC analysis, there were not any cut-off value for nodulesize and SUVmax. Similar results were also obtained for papillary carcinoma as a special subgroup.Conclusion: Characterisation of TIs could not be performed by using age, nodule size and SUVmax. Therefore, TIs which detected byFDG-PET/CT should be examined pathologically due to high risk of malignancy.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Onkoloji; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme